Postcoronary pain and the postmyocardial infarction syndrome. - Williams, R K (1984)
Since non-specific chest pain, which is a common feature after myocardial infarction, may be due to a mild form of Dressler's (postmyocardial infarction) syndrome 80 patients were studied after confirmed myocardial infarction. Two patients had clinical features of classical Dressler's syndrome with high erythrocyte sedimentation rates and strongly positive results for antimyocardial antibodies. Twenty three patients had non-specific chest pain; none had clinical features of Dressler's syndrome. There was no difference in the erythrocyte sedimentation rate between this group and the remainder who had no pain. Equal numbers in each group had weakly positive test results for antimyocardial antibodies; none had a strongly positive result. Thus there appears to be no evidence for a mild form of Dressler's syndrome, and the erythrocyte sedimentation rate and weakly positive results for antimyocardial antibodies are of no diagnostic value in Dressler's syndrome.